Pendinginan Partikel Berbentuk Bola dalam Tumpukan oleh Penguapan Air Permukaan dengan Aliran Udara Paksa dalam Pipa - Budi Rahardjo (agriTECH, 1998)
Fruits and other horticultural products are commonly harvested at high atmospheric temperatures. Since high temperatures significantly make the respiration rate increase and may reduce the quality of the products, the products are necessarily cooled as soon as possible. Accordingly, the objectives of the studies were to develop models for estimating temperature distribution on spherical particles stacked in pipe and cooled by water surface evaporation. The temperature distributions on particles were based on the transient cooling on spheres. The temperature gradient along the pipe was related to the pipe size, particle size, particle position, and air flow rate. Dimensional analysis was used to relate the particle average temperature to the pertinent parameters. The average temperature was calculated using the Heisler chart based on particle center temperature. The results indicate that the average temperatures of the particles can be estimated based on the pertinent parameters. The formulae of the exact solution of the transient heat transfer on spheres can be used to estimate the temperature of the particle during evaporative cooling